2014
DOI: 10.1007/s12010-014-1119-4
|View full text |Cite
|
Sign up to set email alerts
|

Suitable Technological Conditions for Enzymatic Hydrolysis of Waste Paper by Novozymes® Enzymes NS50013 and NS50010

Abstract: Waste paper belongs to a group of quantitatively the most produced waste types. Enzymatic hydrolysis is becoming a suitable way to treat this type of waste and at the same time, to produce a valuable liquid biofuel, because reducing sugars solutions that are formed during the process of saccharification can be a precursor for following or simultaneous fermentation. If it will be possible to make the enzymatic hydrolysis of the waste paper economically viable, it could serve as one of the new ways to lower the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Maitan-Alfenas et al [52] reported that microorganisms are essential in enzyme production for lignocellulosic biomass saccharification. The saccharification process in the ethanol conversion requires less energy and is done in mild conditions at pH of 5.2-6.2 and a temperature range of 45-50 C [53,54]. There are three distinct major types of cellulase enzymes used in the process: (1) endoglucanases (E C 3.2.1.4) hydrolyze at random internal β-1, 4-glucosidic linkages in the cellulose chain producing oligosaccharides of different lengths and with a shorter chain appearance; (2) exoglucanases of cellobiohydrolases (E C 3.2.1.91) progress along cellulose chain ends and release major products as cellulose or glucose; and (3) β-glucosidases known as β-glucoside glucohydrolases (E C 3.2.1.21) hydrolyze cellulose to glucose, liberate cellobiose, soluble cellodextrins to glucose [12,55].…”
Section: Microwave-assisted Alkali Pretreatment Technology and Enzymamentioning
confidence: 99%
“…Maitan-Alfenas et al [52] reported that microorganisms are essential in enzyme production for lignocellulosic biomass saccharification. The saccharification process in the ethanol conversion requires less energy and is done in mild conditions at pH of 5.2-6.2 and a temperature range of 45-50 C [53,54]. There are three distinct major types of cellulase enzymes used in the process: (1) endoglucanases (E C 3.2.1.4) hydrolyze at random internal β-1, 4-glucosidic linkages in the cellulose chain producing oligosaccharides of different lengths and with a shorter chain appearance; (2) exoglucanases of cellobiohydrolases (E C 3.2.1.91) progress along cellulose chain ends and release major products as cellulose or glucose; and (3) β-glucosidases known as β-glucoside glucohydrolases (E C 3.2.1.21) hydrolyze cellulose to glucose, liberate cellobiose, soluble cellodextrins to glucose [12,55].…”
Section: Microwave-assisted Alkali Pretreatment Technology and Enzymamentioning
confidence: 99%